Economic contribution and social welfare of recreational charter boat fisheries in the northeast Atlantic: The cases of Galicia (Spain) and Madeira archipelago (Portugal) - Pablo Pita; Pablo Pita; Gillian B. Ainsworth; Manel Antelo; Lidia Gouveia; Roi Martínez-Escauriaza; Ana Tubío; Sebastián Villasante; Sebastián Villasante (Frontiers in Marine Science, 2022)
Recreational charter boat fisheries provide alternative economic development to traditional commercial fisheries, especially to coastal communities in warm seas. Charter boat fishing has been little studied in temperate regions, and the factors that trigger its development and social contribution to fishing communities are unknown. We performed an economic analysis of recreational charter boat fisheries in the Eastern North Atlantic to assess their contribution to social welfare. We selected two case studies located in Galicia (NW Spain) and Madeira archipelago (Portugal). The two cases differ in the socioecological attributes in which recreational charter boat fishing is developed (e.g., relevance of commercial fishing, tourism, or targeted species), that were included in the assessment. Up to 7 charter fishing companies were identified in Galicia (10 boats) and 14 in Madeira (18 boats), and information on the costs and benefits of the activity were collected by a questionnaire answered by company managers and skippers. Charter boats in Galicia are operating throughout the year, and anglers mostly engage in bottom fishing targeting demersal predators like ballan wrasse (Labrus bergylta) and European seabass (Dicentrarchus labrax) that they retain. Despite the strong seasonality of the fishery in Madeira, focused on summers, the fishing effort is higher than in Galicia. On average, charter boats go fishing for 39.3 ± 41.5 (SD) fishing journeys and take 2 500 anglers on board per year in Galicia, while in Madeira they fish 63.7 ± 32.7 journeys and take 3 200 anglers on board. Anglers target in Madeira pelagic top predators like blue marlin (Makaira nigricans), or some tuna species, e.g., bigeye (Thunnus obesus), by trolling in a catch and release fishery. The economic balance of companies was more favorable in Madeira, with an average gross annual profit of € 28 883 ± 30 755, while economic yield in Galicia was € 4 444 ± 7 916. We also applied a travel cost method to assess the recreation demand of recreational fishing trips based on a questionnaire answered by 150 clients in Galicia and 55 in Madeira. We estimated the visitor surplus mean value to be € 1 385 per year in Galicia (95% confidence interval, CI95%= € 1 219 – € 1 550), and € 1 738 in Madeira (CI95%= € 1 433 – 2 043). The social annual recreation value of Galician fishery was worth € 3.4 Million, ranging between € 3.0 M and € 3.8 M, a value well below the annual economic impact generated by commercial fishing (€ 700 M). The recreation value of the charter boat fishery in Madeira, € 6.3 M, ranging between € 5.2 M and € 7.5 M, is comparable to the annual economic impact of commercial fishing, that contributes to the local economy with € 12 M.